Transnational coupling in the age of nation making during the 19th and 20th centuries - Leopoldie, Nicole (Anthem intercultural transfer studies., 2023)
Transnational Coupling in the Age of Nation Making during the 19th and 20th Centuries examines and compares courtship and marriage patterns that occurred between France and the United States during the 19th and 20th centuries. Departing from state-centered studies of marriage law, it draws on the methodologies of transnational history, cultural history and the history of emotion to show that these unions were part of a broader pattern of the larger cultural love affair between the two societies.